JENIS DAN KEPADATAN TIKUS DI PANTI ASUHAN “X” KOTA SEMARANG - Rani Kristiana Putriosa Saragih; Martini Martini; Udi Tarwatjo (Jurnal Kesehatan Masyarakat (Undip), 2019)
Mice are wild animals that are often associated with human life. The high rat population can have an impact on various areas of human life. Mice can also transmit several other diseases including murine typhus, leptospirosis, salmonellosis, richettsial pox, rabies, and trichinosis. This study was conducted to determine the type and density of mice, ectoparasites found in mice, sanitation and clean behavior patterns in orphanages " x "Semarang city. The type of this research is descriptive research with cross sectional method. Knowledge of rat species is very important to know the type and density of mice which is the initial information for controlling and preventing dangerous diseases. The sample in this study were all rats caught at the "X" Orphanage using 40 live traps for 5 consecutive days. Trap success at the Orphanage is 8% for the area in the Orphanage 3% and outside the Orphanage 5%, so that the trap success obtained is included in the high or solid category of rats. A total of 16 rats caught in the Orphanage with the type of rats caught were Bandicota, sp 6 tails (37.5%), Mus musculus 6 tails (37.5%) and Rattus norvegicus 4 tails (25%). The mice that were mostly caught in the Orphanage were in the Outer Orphanage habitat as many as 10 (62.5%). Gender Mice which were mostly caught were 10 female mice (62.5%). The type of ectoprasite found in mice caught was Cimex, sp. Environmental conditions and environmental sanitation are not clean. The behavior of clean living in orphanages is also still far from the standard of clean living and a healthy lifestyle. It is expected that sanitation and environmental conditions can be healthier and cleaner.